The Boundary Rigidity of Lattices in Products of Trees - Jankiewicz, Kasia; Karrer, Annette; Ruane, Kim; Sathaye, Bakul (Topology Proceedings, 2024)
We show that every group acting properly and cocompactly by isometries on a product of $n$ bounded valance, bushy trees is boundary rigid. That means that every $\operatorname{CAT}(0)$ space that admits a geometric action of any such group has the visual boundary homeomorphic to a join of $n$ copies of the Cantor set.